Performance Analysis of S-MAC Protocol in Wireless Sensor Network - Bishnoi, Deepika; Kumar Nandal, Sunil (International Journal of Computer Sciences and Engineering, 2025)
Wireless sensor network has become a leading area of research because of its various applications such as environmental monitoring, target detection and tracking, health monitoring, industrial process monitoring, energy efficiency, disaster management and military security system. In a Wireless sensor network, the capacity of a battery of small size sensors is restricted and once the sensor nodes work, it consumes extra energy which is depending on the batteries. Sensor node performs the operation of computation and communication through which consumption of energy get exhausted at the faster rate. Energy efficiency is an important requirement in a wireless sensor network. Most of the energy is consumed in the communication part of the sensor node. Medium access control protocol plays an important role in energy consumption for wireless sensor network. MAC protocols have the capability to maintain real time functionality and achieve energy efficiency. The S-MAC protocol is used for increasing sleep duration, overhearing and decreasing idle listening, the collision of packets or eliminating hidden terminal problem which is a help to increase energy efficiency. The aim of this paper is to study S-MAC protocol in wireless sensor network. The objective of this work is to find the best-suited performance of S-MAC protocol in the term of energy efficiency, throughput, latency, etc. in wireless sensor network.